THE DETERMINATION OF PLANNING PERIODS TO THE TRAIN FORMATION - Kuznetsov, V. H.; Erofeiev, O. O. (Science and Transport Progress, 2007)
The problem of definition of the settlement periods of planning for various conditions trains makeup is put. The factors influencing durations of the period of planning are established. The design procedure of range trains makeup and the period of the integrated planning trains makeup for the established range is considered. The methodical positions are given, allowing to establish the periods of routine planning trains makeup and the periods trains makeup the developed plans. The problem of reliability of the information in system of formation of trains is considered. Groups of events in system of planning are allocated. For each group the reasons which conduct to decrease of reliability of the information are established. The design procedure of reliability of the information in system trains makeup is given. It is determined influence reliability of the information for the periods of planning. The technique of definition of limiting value of the period of planning is given on reliability of the acting information. Recommendations for increase of reliability for each of the allocated groups of events are given.